Perbandingan Algoritma BWT Dan Algoritma Levenstein Dalam Mengkompresi File PDF - Siregar, Desi Novria (STMIK Budi Darma, 2024)
Nowadays, developments in science are increasingly rapid and rapid. These developments change the way humans search for sources of information. The need for information cannot be separated from people's daily lives. The source of information obtained is not only through print media but also electronic media such as e-books (digital books). One technique that can be used to overcome this problem is the use of compression techniques to reduce its size or often called compression techniques. One of the uses of compression techniques is to reduce the space capacity in storage media. Compression is reducing the size of data to a size smaller than the original. Compressing this data is very beneficial when there is data that is very large in size and the data contains many repeated characters, it will be more efficient in storage. This research produces a performance level of the compression algorithm, which will measure the performance of the PDF file compression results according to predetermined parameters. From the calculations that have been calculated, it can be concluded that the percentage of PDF file compression results using the BWT algorithm is 101.06% and the Levenstein algorithm is 101.34%.